2016
DOI: 10.1002/jcla.21956
|View full text |Cite
|
Sign up to set email alerts
|

Reference Intervals of Routine Coagulation Assays During the Pregnancy and Puerperium Period

Abstract: We presented reference intervals for coagulation assays from the nonpregnancy to puerperium period that can be adopted in other laboratories after further validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 17 publications
5
15
1
3
Order By: Relevance
“…Coagulability gradually increases from the first to third trimesters [1] in pregnant women, becoming higher than in normal women [2] . Consistent with this, late pregnancy is characterized not only by changes in hormone secretion and liver metabolism, but higher coagulation indices [3] .…”
Section: Introductionsupporting
confidence: 65%
“…Coagulability gradually increases from the first to third trimesters [1] in pregnant women, becoming higher than in normal women [2] . Consistent with this, late pregnancy is characterized not only by changes in hormone secretion and liver metabolism, but higher coagulation indices [3] .…”
Section: Introductionsupporting
confidence: 65%
“…Levels of alkaline phosphatase (ALP) rise due to production of placental isoenzyme, as well as a significant increase in bone isoenzyme in third trimester . Most studies have found that prothrombin time (PT) falls progressively from second trimester such that values are approximately 10–20% lower than pre‐conception values in third trimester . This may be important when considering abnormal hepatic synthetic function with disorders such as AFLP.…”
Section: Laboratory Investigationsmentioning
confidence: 81%
“…33,34,64,65,71,74 Most studies have found that prothrombin time (PT) falls progressively from second trimester such that values are approximately 10-20% lower than pre-conception values in third trimester. 33,75,76 This may be important when considering abnormal hepatic synthetic function with disorders such as AFLP. Serum amylase activity does not change significantly during pregnancy.…”
Section: Liver Testsmentioning
confidence: 99%
“…The diagnosis of DIC in pregnancy requires a high index of suspicion, due to various laboratory changes in the gravid patient which make its diagnosis more challenging ( Table 1 ). These changes include hyperfibrinogenemia (normal 3 rd trimester value of approximately 5 g/L), decreased prothrombin (PT) and partial thromboplastin times (aPTT), and thrombocytopenia [ 1 , 4 , 5 , 14 , 15 ]. Therefore, hematologic laboratory results that align with normal values in the nongravid patient should elicit additional scrutiny by the clinician.…”
Section: Discussionmentioning
confidence: 99%